Clinical Management of Insect Bite Local Reactions (Keeta Damsha) using a Traditional Herbal Formulation (Rahas Beheth Guliya): An Observational Case Study - Bandara, S.M.B.Y.; Wimalasiri, Y.S.G.; Rasangika, K.W.; Keerthisinghe, S.M.M.D. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Agada tantra is one amongst the eight-fold branches of Ayurveda that deals with identification, prevention, diagnosis and treatment of various manifestations caused by Visha. Keeta visha is classified under Jangama visha and many groups of insects can be identified as Keeta. Keeta visha manifest local symptoms to severe systemic reactions in the human beings, even death. Therefore, identify a treatment modality for Keeta damsha (insect bites) is highly needed. Even though, there were hardly found effective user-friendly medications for treating Keeta visha a text named Vishavaidya Chintamaṇi; Traditional Visha chikitsa in Sri Lanka; has mentioned a traditional formulation, Rahas beheth guliya. The study was designed to identify the effectiveness of the RBG on Keeta Visha. This case study documents the treatment of a 55-year-old female patient diagnosed with Keeta damsha, exhibiting classical signs of localized toxicity. A traditional formulation; Rahas beheth guliya, was administered with lime juice and applied topically as mentioned in Vishavaidya Chintamaṇi. Rahas beheth guliya resulted in significant improvement in inflammation, itching, and erythema by the second clinical visit. The observed therapeutic response supports the traditional use of Rahas beheth guliya in managing minor toxicological manifestations. It is intended to further utilize in the similar clinical cases and conduct comprehensive chemical analyses of Rahas beheth guliya to further validate and characterize its pharmacological properties.
Keywords: Keeta damsha; Rahas beheth guliya; Ayurveda toxicology; Insect bite